Deep Problems in Shallow Lakes: Why Controlling Phosphorus Inputs May Not Restore Water Quality - Karl Havens (EDIS)
Florida’s thousands of lakes are shallower than most people realize, and some unique properties of shallow lakes make them challenging to restore if they have been degraded by nutrients or other pollutants. This 4-page fact sheet examines how water managers track nutrients as they cycle through Florida’s lakes. Written by Karl Havens, and published by the UF Department of Sea Grant, January 2013.